The Influence of Transformational Leadership and Organizational Culture On The Performance of Elementary School Teachers In Bekasi Regency Through Teacher Innovation As A Mediating Variable - Rayhan Achmad; Retno Purwani Setyaningrum; Sunita Dasman (Dinasti International Journal of Education Management And Social Science, 2024)
School is a structured system, because schools have components related to each other. The components that are discussed in this case are employees or teachers. The purpose of this study is to create and develop an empirical conceptual model of how transformational leadership and organizational culture can affect performance with innovation as a mediating variable. Sampling is carried out with the sampling technique used in this study is random sampling (probability sampling), namely by simple random sampling. This study used quantitative data with the distribution of questionnaires processed using PLS Software. The results of this study are first, transformational leadership has a positive and significant effect on the performance of elementary school teachers in Bekasi Regency. Second, organizational culture has a negative and insignificant effect on the performance of elementary school teachers in Bekasi Regency. Third, transformational leadership has a positive and significant effect on the innovation of elementary school teachers in Bekasi Regency. Fourth, organizational culture has a positive and significant influence on the innovation of elementary school teachers in Bekasi Regency. Fifth, Innovation has a positive and significant effect on the performance of elementary school teachers in Bekasi Regency. Sixth, transformational leadership has a negative and insignificant effect on performance through the innovation of elementary school teachers in Bekasi Regency. Seventh, organizational culture has a negative and insignificant effect on performance through the innovation of elementary school teachers in Bekasi Regency.